Racial disparities and temporal trends in dementia misdiagnosis risk in the United States - Kan Z. Gianattasio; Christina Prather; M. Maria Glymour; Adam Ciarleglio; Melinda C. Power (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Systematic disparities in misdiagnosis of dementia across racial/ethnic groups have implications for health disparities. We compared the risk of dementia under‐ and overdiagnosis in clinical settings across racial/ethnic groups from 2000 to 2010. Methods We linked fee‐for‐service Medicare claims to participants aged ≥70 from the nationally representative Health and Retirement Study. We classified dementia status using an algorithm with similar sensitivity and specificity across racial/ethnic groups and assigned clinical dementia diagnosis status using ICD‐9‐CM codes from Medicare claims. Multinomial logit models were used to estimate relative risks of clinical under‐ and overdiagnosis between groups and over time. Results Non‐Hispanic blacks had roughly double the risk of underdiagnosis as non‐Hispanic whites. While primary analyses suggested a shrinking disparity over time, this was not robust to sensitivity analyses or adjustment for covariates. Risk of overdiagnosis increased over time in both groups. Discussion Our results suggest that efforts to reduce racial disparities in underdiagnosis are warranted.